Osteoarthritis and Total Joint Arthroplasty in Housing-Insecure Patients at a Safety Net Hospital in a Major Urban City - Abbott Gifford, BA; Kelechi Nwachuku, MD; Lisa Bonsignore-Opp, MD; Paul Toogood, MD, MS; Derek Ward, MD (Arthroplasty Today, 2025)
Background: Osteoarthritis is the leading cause of disability among older adults in the United States. People experiencing homelessness (PEH) face worse health outcomes and higher rates of musculoskeletal diseases than housed individuals. Despite this burden, PEH often lack access to orthopaedic care. This project examines surgical outcomes among PEH and investigates where in the care process barriers to access may exist. Methods: New patient visits to the Zuckerberg San Francisco General Hospital Arthroplasty Clinic in 2022 were examined to establish a retrospective cohort. Patients were grouped by housing status, and data on demographics, disease severity, and comorbidities were collected. Analysis was performed using descriptive statistics and logistic regression. Presentation rate was calculated among clinic-presenting PEH and compared to a similarly captured population of patients on the San Francisco Health Plan. Results: Of 250 patients, 4 were unhoused and 41 were unstably housed. PEH and housing insecurity had worse Kellgren–Lawrence scores, higher rates of substance use, mental illness, HIV, and hepatitis C virus than stably housed patients. There were no differences in surgical progression, emergency department visits, readmission, reoperation, or follow-up. Significantly fewer PEH presented to clinic compared to those on the San Francisco Health Plan (X2 = 11.37, P = .0007). Conclusions: No differences in progression to surgery or surgical outcomes were found between housing groups. PEH accessed arthroplasty services less frequently than housed individuals. These findings suggest that PEH from the study population may be good surgical candidates and have limited access, but conclusions are limited by a short study follow-up.